2009
DOI: 10.1016/j.neuropsychologia.2009.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of extrastriate body and biological-motion selective areas by manipulation of visual-motor congruency

Abstract: To date, several posterior brain regions have been identified that play a role in the visual perception of other people and their movements. The aim of the present study is to understand how these areas may be involved in relating body movements to their visual consequences. We used fMRI to examine the extrastriate body area (EBA), the fusiform body area (FBA), and an area in the posterior superior temporal sulcus (pSTS) that responds to patterns of human biological motion. Each area was localized in individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 38 publications
(51 reference statements)
5
47
0
Order By: Relevance
“…In Experiment 3, a scene-selective region of transverse occipital sulcus (TOS;Epstein et al, 2005) was also defined, by contrasting the response to scenes with that to images of chairs. Peak voxels were selected within anatomical regions referring to previous studies (Epstein et al, 2005;Kontaris et al, 2009) and used to position the TMS coil (mean coordinates ϭ 33 (1.1), Ϫ77 (2.0), 14 (1.8)).…”
Section: Methodsmentioning
confidence: 99%
“…In Experiment 3, a scene-selective region of transverse occipital sulcus (TOS;Epstein et al, 2005) was also defined, by contrasting the response to scenes with that to images of chairs. Peak voxels were selected within anatomical regions referring to previous studies (Epstein et al, 2005;Kontaris et al, 2009) and used to position the TMS coil (mean coordinates ϭ 33 (1.1), Ϫ77 (2.0), 14 (1.8)).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, fMRI studies on the imitation-inhibition task so far did not reveal activation in EBA/MT Kontaris, Wiggett, & Downing, 2009;Spengler et al, 2010;). We think that this is due to the fact that fMRI is less sensitive to such subtle changes.…”
Section: The Effect Of Action On Perceptionmentioning
confidence: 97%
“…In addition, we used the ''related articles'' function on PubMed to identify additional papers. This search revealed seven additional papers (Corradi-Dell'Acqua et al 2008;Kontaris et al 2009;Matsuzawa et al 2005;Nahab et al 2010;Spengler et al 2009;Yomogida et al 2010;Tsakiris et al 2010) making a total of 31 studies.…”
Section: Studies Selectionmentioning
confidence: 99%
“…For example Farrer and Frith (2002) and Farrer et al (2003) reported greater insula activation for self-versus other-agency attribution, Leube and coworkers (2003a, b) found a negative correlation between putamen activity and the extent of temporal delay of the visual feedback, Kontaris et al (2009) showed activation in parieto-occipital sulcus for congruent compared to incongruent feedback while other studies did not report any significant activation when directly comparing conditions of coherent versus distorted feedback (Bralslev et al 2006;David et al 2007;Nahab et al 2010). …”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation